Implementasi Assesmen Akidah Akhlak pada Lembaga Pendidikan Madrasah Ibtidaiyah Misbahul Adhim dalam Era Digital - Binti Khoirur Rofiah; Romelah Romelah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Faith and moral education in Madrasah Ibtidaiyah (MI) plays an important role in shaping students' moral character in accordance with Islamic principles. Amidst the explosive growth of digital technology, Madrasah Ibtidaiyah Misbahul Adhim implements faith and moral assessment using various digital platforms, namely Moodle and Quizz. This study aims to explore the implementation of faith and moral assessment in the digital era at Madrasah Ibtidaiyah Misbahul Adhim, and to identify its benefits, challenges, and impacts on student learning. By applying case study methodology, qualitative approach, and data collection strategies that include document analysis, observation, and interviews, the following study found that although technology makes it easier to carry out assessments, challenges such as accessibility, content supervision, and interaction quality must still be considered. Therefore, this study suggests the need for stricter supervision of digital content and training for teachers to optimize technology in faith and moral assessments.